Perspektif Amin Abdullah tentang Integrasi-Interkoneksi dalam Kajian Islam - Siswanto, Siswanto (TEOSOFI: Jurnal Tasawuf dan Pemikiran Islam, 2013)
This article peeling Amin Abdullah?s thinking about integration and interconnection methods in studying religion. Amin Abdullah has a great project to reconcile between religion and science as part of an attempt to break the deadlock of the problems of the present. So from a variety of scientific disciplines was not just to a single entity attitude (arrogance of science: the only one that feels most right), isolated entities (of various scientific disciplines happen ?isolation? , no scolds greet each other), but rather to the interconnected entities (aware of the limitations of their respective disciplines, resulting in mutual cooperation and is willing to use his methods even though it comes from another clump of science). With the model of integration and interconnection, Amin Abdullah has been able to show that the religious sciences can greet each other with other general sciences, because in essence is one. That science is beneficial for human beneficiaries.